Indigenous peoples atlas of Canada: First Nations - Royal Canadian Geographical Society (Royal Canadian Geographical Society, 2018)
Created in partnership with the Assembly of First Nations, Inuit Tapiriit Kanatami, the Métis Nation, the National Centre for Truth and Reconciliation and Indspire